Socio-economic Determinants of Turkey Production among Nigerian Soldiers - Mbanasor, J.A.; Sampson, A. (International Journal of Poultry Science, 2004)
The socio-economic situation of the country has given rise to increased agricultural activities not only among the civilian population but also among the members of the Nigerian Army. According to World Bank, Poverty in Nigeria has increased dramatically with 66% of the population living below National Poverty line, compared with 43% in 1992. This has socio-economic implications to the Nigerian army as well. As a result, many soldiers have resorted to selected agricultural enterprises especially Turkey production as a way of alleviating the economic situation. A total of 60 soldiers covering all the ranks and file of the Nigerian Army were randomly selected from the 82 Division of the Nigerian Army. Four barracks were purposely selected due to their interests in Turkey Production. The barracks include Eburutu Barracks Calabar, Abakpa- Enugu, Zamani lekwot cantonment PH and 82-Division Records, Abakaliki. Data generated were analyzed using regression analysis, benefit-cost ratio, and descriptive statistic. The major factor that enhanced turkey production among soldiers were income and previous farming experience. The enterprise was not only profitable but also viable. Efforts should be made to encourage more soldiers to embrace this enterprise.